The Impact of Cashless Payment on Indonesian Economy: Before and During Covid-19 Pandemic - Irvi Givelyn; Siti Rohima; Mardalena Mardalena; Fera Widyanata (Jurnal Ekonomi Pembangunan, 2022)
This study aims to analyze the impact of cashless payments on Indonesia’s economy, before and during the COVID-19 pandemic. The economic growth in this study is calculated through GDP at constant price and the cashless payment in this study are represented by transactions through debit card, credit card, and e-money. The data used in this study uses secondary data in the form of time series data from January 2018 to December 2022. The data was obtained from the Central Bank of Indonesia (BI) statistic data and Statistics Indonesia (BPS). The analytical method used in this study is the Autoregressive Distributed Lag (ARDL). Based on the results of estimations indicate that in the short run as well as in the long run, debit card and credit card have an insignificant impact on economic growth, while e-money has a positive and significant impact. Cashless payment has a significant positive impact on economic growth, before and during COVID-19 pandemic, however during the pandemic, the impact of cashless payment on economic growth was bigger. As a result, the current cashless policy should be modified to create an efficient payment system while also considering the impact of using cashless payment instruments during the COVID-19 pandemic.